E-mail laws changing. - Ritter, Robert (Quill)
Discusses three court cases focusing on electronic libel, freedom of information and privacy in electronic mail systems. Journalists' use of bulletin board services; Need to protect electronic records not existing in paper form; Protection provided by the Electronic Communications Privacy Act; Suggestions for electronic mail users. INSETS: Resources.;Plugging in..